WHO MAKES ADOLESCENTS HAPPY? AN EXPLORATIVE STUDY USING THE INDIGENOUS PSYCHOLOGY APPROACH - Hamka, Annisa Soleha; Yuniarti, Kwartarini Wahyu; moordiningsih, Moordiningsih; Kim, Uichol (Universitas Muhammadiyah Surakarta, 2015)
This study is aimed at discovering who the source of happiness is for adolescents and how he or she accomplishes his or her role in creating happiness. A number of 458 senior high school students completed an open-ended questionnaire developed by Kim and Park (2008). An indigenous approach is used to analyse respondentsâ answers to the open-ended questionnaire. A categorization of respondentsâ answers and cross tabulation is also conducted. Analysis results show that a majority of adolescencesâ source of happiness derives from the family (50.1%), and friends (27%). Their role in creating happiness was by supporting (54.3). Acceptance of adolescents (20.8%) was also a source of happiness for adolescents. Providing facilities and prayers was also a role given for adolescents.